Developing a model for promoting media literacy skills for an aging society through family participation - Phiraya Tongchalerm; Pariya Pariput (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This research project is on developing a media literacy model for the elderly with a focus on family participation. The study had three main objectives: (1) to examine the problems and needs of the elderly in Sang Tho Sub-district, (2) to develop a media literacy promotion model, and (3) to evaluate the quality of the model. The findings revealed that elderly individuals faced challenges using media platforms like Facebook and YouTube. These issues negatively affected their health and made them vulnerable to misinformation and online fraud. The researchers developed a media literacy model for the elderly with six main components: foundational principles, objectives, curriculum, learning activities, assessment, and a support system. The model integrates the Media and Information Literacy and Dialogue (MIDL) framework, adult learning theory, and participatory learning. It focuses on four key skills: access, analysis and evaluation, content creation, and application for transformation. The learning activities are based on the